EMOTIONAL FEATURES OF TEACHERS UNDER REMOTE WORK DURING PANDEMIC PERIOD - Ogannisyan , L. A. (Modern Psychology, 2021)
The professional activity of a teacher is one of the most stressful. The transition to a remote form of work, due to the restrictions during the pandemic, gave rise to special emotional stress among teachers, caused by a number of factors. In the current circumstances, the emotional sphere of the teacher, the influence of which on the effectiveness of achieving educational objectives has been proven by numerous studies, is again in the spotlight. In connection with the above, the purpose of our study is to study the characteristics of the emotional sphere of teachers in the conditions of remote work during a pandemic. Research methods: R. Ketell's 16-factor personality questionnaire (block of emotional-volitional qualities; adaptation by AN Kapustina), "Scale of differential emotions" (K. Izard, adaptation by AB Leonova), methods of mathematical statistics. Sample: teachers of secondary vocational schools in Rostov- on-Don, in the amount of 53 people (from 30 to 45 years old). As a result of the study, it was proved that teachers during the period of distance work are distinguished by emotional instability, increased anxiety, self-doubt, doubts and suspiciousness, low self-regulation, low control of emotions and behavior, stress resistance, as well as a higher degree of expression of "fear" and "shame ".
Keywords: emotions; emotional characteristics of teachers; distance education.